Evaluasi Penerapan Manajemen Layanan TI Menggunakan Framework COBIT 5 pada Subdomain APO09 Manage Service Agreements (Studi Kasus : Satuan Organisasi XYZ - Lembaga ABC) - Cindy Anastasia Kasodu; Augie David Manuputty; Sakiwan Sakiwan (Maranatha University Press, 2018)
Application of Information Technology system in organization needed well management of Information Technology service in order to produce more values for the organization and an increase in quality of service provider. XYZ organization had a duty to do infrastructure management and managing the order of Information Technology, developing of information system and standard arranging. One of the strategic target to gain a goal of XYZ organization was doing a modernization of all Technology of Information and Combination (TIC) facilities and service in ABC institution. Along with increasing user dependence on IT service in ABC institution, thus XYZ organization applies Management System of Information Technology Service (MSITS) based on ISO 20000. XYZ organization must measure the maturity level of MSITS implementation using COBITS 5. To gain the data, qualitative method and interview to the XYZ organization about MSITS were needed. This research used COBIT 5 framework which focused on APO09 subdomain. The result of APO09 subdomain was 88% in level 1 (Performed Process).